Assessing constitutional performance - Ginsburg, Tom; Huq, Aziz Z. (New York, NY : Cambridge University Press, 2016)
"From London to Libya, from Istanbul to Iceland, there is great interest among comparative constitutional scholars and practitioners about when a proposed constitution is likely to succeed. But what does it mean for a constitution to succeed? Are there universal criteria of success, which apply across the board? Or is the choice of criteria entirely idiosyncratic? This edited volume takes on the idea of constitutional success and shows the manifold ways in which it can be understood. It collects essays from philosophers, political scientists, political scientists, empiricists, and legal scholars, that approach the definition of constitutional success from many different angles. It also brings together case studies from Africa, Europe, Latin America, the Middle East, and Asia. By exploring a varied array of constitutional histories, this book shows how complex ideas of 'constitutional success' play out differently in different contexts and provides examples of how "success" can be differently defined under different circumstances"--
Assessing constitutional performance / Tom Ginsburg and Aziz Z. Huq -- Hippocratic constitutional design / Aziz Z. Huq -- What is a good constitution? Assessing the constitutional proposal in the Icelandic experiment / Helene Landemore -- When is a constitution doing well? The Alberdian test in the Americas / Roberto Gargarella -- Parties and constitutional performance / Martin Shapiro - Constitutional performance in transitions from military to civilian rule / Ozan O. Varol -- Constitutional permissiveness, constitutional restrictiveness, and religious freedom / Hanna Lerner -- Performance of constitutions : transitional provisions / Sumit Bisarya -- Time and constitutional efficacy / Zachary Elkins, Tom Ginsburg and James Melton -- Competitive democracy and the constitutional minimum core / Rosalind Dixon and David Landau -- Ambedkar's constitution : promoting inclusion, opposing majority tyranny / Martha C. Nussbaum -- Assessing the constitutionn of Kenya 2010 fie years later / James Thuo Gathii -- The Arab Spring constitutions : for whose benefit? / Zaid Al-Ali -- Stability in flexibility : a British lens on constitutional success / Erin F. Delaney.
Includes bibliographical references (pages 417-420) and index.
Keywords: Constitutional law; Constitutional history; Comparative law; LAW / Constitutional